2020
DOI: 10.1002/jlcr.3879
|View full text |Cite
|
Sign up to set email alerts
|

Production of [68Ga]Ga‐PSMA: Comparing a manual kit‐based method with a module‐based automated synthesis approach

Abstract: The labeling of peptides with gallium-68 is often initially performed by manual labeling, but with high clinical demand, other alternatives are needed. Coldkits or automated synthesis are viable options for standardized methods and deemed pharmaceutically more acceptable. This study compares these [ 68 Ga] Ga-PSMA-11 production methods. Data from 40 kit-based and 40 automated syntheses of [ 68 Ga]Ga-PSMA-11 were analyzed. Pre-set criteria were evaluated including radiochemical purity, radionuclidic purity, che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Compared with other diagnostically used tracers, the value is rated as high, especially for radiometal-based conjugates. For comparison, an apparent molar activity ≥ 18.5 GBq/µmol to 35.5 GBq/µmol is usually exhibited for clinically applied [ 68 Ga]Ga-PSMA-11 [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other diagnostically used tracers, the value is rated as high, especially for radiometal-based conjugates. For comparison, an apparent molar activity ≥ 18.5 GBq/µmol to 35.5 GBq/µmol is usually exhibited for clinically applied [ 68 Ga]Ga-PSMA-11 [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, this, plus shorter production time and higher radiolabeling yield with the kit than with automated module synthesis, might allow for multiple patient preparations, although kits are usually recommended as single-dose preparations ( 118 , 124 , 125 ). Regarding outcomes of both processes, in terms of product characteristics, quality control gave comparable results ( Figure 6A ), and both methods are reliable and comply with Good Manufacturing Practices and European Pharmacopeia specifications ( 113 , 124 , 126 , 127 ). In terms of clinical applications, a direct comparison on patients with prostate cancer found no significant differences in PET/CT image quality ( Figures 6B,C ) ( 126 ).…”
Section: Cold Kitsmentioning
confidence: 68%
“…They reported 70 and 132 μSv for the automated labeling (left and right hand) and 179 and 152 μSv for the kit-based preparation. In the study by Kleynhans et al on [ 68 Ga]Ga-HBED-CC-PSMA-11 synthesis, whole-body exposure was found to be significantly lower for the automated synthesis with 2.05 ± 0.99 μSv vs. 14.32 ± 5.3 μSv per synthesis ( 127 ). However, automated synthesis was performed on a hot cell with 50-mm lead shielding, while the kit preparation was realized in a 3-mm lead-shielded class II biosafety cabinet, with a 10-mm lead shielded tabletop shield.…”
Section: Cold Kitsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Kleynhans group recently compared kit- and module-based production of 68 Ga-PSMA-11 . The study analyzed 40 preparations of 68 Ga-PSMA-11 from each method.…”
Section: Ga-kits: Nuclear Medicine Applicationsmentioning
confidence: 99%